Unplanned Emergency and Urgent Care Visits After Outpatient Orthopaedic Surgery. (20th September 2021) - Williams, Benjamin R.; Smith, Lauren C.; Only, Arthur J.; Parikh, Harsh R.; Swiontkowski, Marc F.; Cunningham, Brian P.
Abstract : Introduction: This study sought to determine (1) incident risk, (2) chief report, (3) risk factors, and (4) total cost of unplanned healthcare visits to an emergency and/or urgent care (ED/UC) facility within 30 days of an outpatient orthopaedic procedure. Methods: This was a retrospective database review of 5, 550 outpatient surgical encounters from a large metropolitan healthcare system between 2012 and 2016. Statistical analysis consisted of measuring the ED/UC incident risk, respective to the procedures and anatomical region. Patient-specific risk factors were evaluated through multigroup comparative statistics. Results: Of the 5, 550 study patients, 297 (5.4%) presented to an ED/UC within 30 days of their index procedure, with 23 (0.4%) needing to be readmitted. Native English speakers, patients older than 45 years, and nonsmokers had significant reduced relative risk of unplanned ED or UC visit within 30 days of index procedure ( P < 0.01). In addition, hand tendon repair/graft had the greatest risk incidence for ED/UC visit (11.0%). Unplanned ED/UC reimbursements totaled $146, 357.34, averaging $575.65 per visit. Discussion: This study provides an evaluation of outpatient orthopaedic procedures and their relationship to ED/UC visits. Specifically, this study identifies patient-related and procedural-related attributes that associate with an increased risk for unplanned healthcare utilization.